We Know a Lot, but Not Nearly Enough: Introduction to the CJCCJ Special Issue on Desistance - McCuish, Evan C. (Canadian journal of criminology and criminal justice, 2020)
Desistance is now one of the main criminal career parameters investigated by criminologists. Similarly, practitioners working within the criminal justice system are primarily focused on ways to promote desistance among their clients. However, these two groups typically think about desistance in different ways. Practitioners are often exposed to the idea from correctional psychology that desistance is the absence of recidivism. Criminologists typically consider desistance to be a process that includes recidivism. The purpose of this special issue was to present a criminological viewpoint of desistance. Authors of each article identified an area that they felt was a key or emerging theme in desistance research. This article introduces the topic of desistance, highlights how the articles in this special issue contributed to desistance research and have implications for criminal justice system practices, and ends with a call for future research on the measurement of human agency, structural and historical contexts that influence human agency, and whether human agency moderates the relationship between informal social control and desistance. (English)